Polyphenolic characteristics, antimicrobial and antioxidant activity of Zingiber neesanum (Graham) Ramamoorthy rhizomes and identification of volatile metabolites by GC-MS analysis. Issue 17 (19th August 2021) - Aswati Nair, R.; Ganapathy, G.; Harshitha, K.
Abstract: Rhizomes of Zingiber neesanum (Graham) Ramamoorthy, endemic to Western Ghats and subject to few studies, were analysed for bioactivity and phytochemical composition. High total tannin (TT) content in isopropanol extract [55.261 ± 6.623 mg TAE.100 g –1 DW] contributed to antimicrobial activity against gram negative Enterococcus fecalis (21.7 ± 0.6 cm) while high total flavonoid (TF) content in ethyl acetate extract [681.94 ± 33.87 mg CE.100 g −1 DW] accounted for the antifungal activity against Mucor rouxii (9.7 ± 0.6). Isopropanol extracts also showed high anti-oxidant activity as determined by DPPH and FRAP assays. Major bioactive phytochemical constituents in Z. neesanum rhizome identified by GC-MS analysis included 2-Methyl-7-nonadecene (13.99%; antimicrobial), Actinomycin C2 (8.57%; antineoplastic) and Deoxyspergualin (12.55%; immunosuppressive). Graphical Abstract: UF0001